Comparison of biosimilar filgrastim with originator filgrastim for peripheral blood stem cell mobilization and engraftment in patients with multiple myeloma undergoing autologous stem cell transplantation. Issue 11 (14th July 2015) - Pham, Tina; Patil, Sushrut; Fleming, Shaun; Avery, Sharon; Walker, Patricia; Wei, Andrew; Curtis, David; Stuart, Georgia; Klarica, Daniela; O'Brien, Maureen; Morris, Karen; Das, Tongted; et al.
Abstract : BACKGROUND: Nivestim is a biosimilar approved for the same indications as Neupogen including the mobilization of autologous peripheral blood stem cells (PBSCs). The clinical efficacy and safety of Nivestim for this use have not been formally assessed in clinical trials. STUDY DESIGN AND METHODS: In our retrospective single‐center study we compared variables of PBSC mobilization and engraftment of 60 patients mobilized with Nivestim to that of 38 patients mobilized with Neupogen. RESULTS: We found no difference between Nivestim and Neupogen in peripheral blood CD34+ at first leukapheresis (47 × 10 6 cells/L vs. 60 × 10 6 cells/L, p = 0.48) nor the total CD34+ collected (5.37 × 10 6 /kg vs. 4.59 × 10 6 /kg, p = 0.22). However, a difference in the median number of leukapheresis procedures (one vs. two, p = 0.0007) was observed. Eighty‐one patients (51 Nivestim and 30 Neupogen mobilized) went on to transplantation. Median time to neutrophil engraftment (15 days vs. 13.5 days, p = 0.09) and platelet (PLT) engraftment (20 days vs. 18 days, p = 0.01) was longer in the Nivestim group. The significant delay in PLT engraftment did not, however, translate to increased PLT transfusions (two vs. three, p = 0.2) or impact significantly on hospitalization time for admissions within 30 days posttransplant (20 days vs. 18 days, p = 0.17). CONCLUSION: Nivestim is as effective as Neupogen for PBSC mobilization; however, its use was associated with a delay in PLT recovery. A prospective study should be conducted to confirm our findings.